2012
DOI: 10.1037/a0027726
|View full text |Cite
|
Sign up to set email alerts
|

Severity of mental health impairment and trajectories of improvement in an integrated primary care clinic.

Abstract: Patients treated within an integrated primary care behavioral health service demonstrate significant improvements in clinical status, even those with the most severe levels of distress at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
62
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 37 publications
(54 reference statements)
14
62
0
Order By: Relevance
“…Furthermore, our follow-up rates were similar to those found in other IBHC models (Bryan et al, 2012; Corso et al, 2012). In particular, we found that approximately 28.0% of Latino patients and 34.7% of non-Latino White patients attended their scheduled follow-up sessions, which is similar to the 29.8% attendance rate found by Bryan and colleagues (2012) and the 28.4% found in Corso and colleagues (2012).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, our follow-up rates were similar to those found in other IBHC models (Bryan et al, 2012; Corso et al, 2012). In particular, we found that approximately 28.0% of Latino patients and 34.7% of non-Latino White patients attended their scheduled follow-up sessions, which is similar to the 29.8% attendance rate found by Bryan and colleagues (2012) and the 28.4% found in Corso and colleagues (2012).…”
Section: Discussionsupporting
confidence: 88%
“…The two groups indicated that they were approaching levels of distress at their last BHC session that were in the mild or normal range of functioning. Given that patients who are more distressed at baseline tend to improve more in IBHC than those who are less distressed (Bryan et al, 2012) and that Latino patients referred for IBHC services showed lower levels of distress at baseline than non-Latino patients, one might have expected Latinos not to improve at a comparable rate with integrated behavioral health interventions. In this regard, our results are consistent with others (e.g., Sue, 1988) who find all patients, regardless of race or ethnicity, benefit similarly from psychological treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without these factors, the fidelity and commitment to the PCBH model could not have been sustained. The implementation of the PCBH model in the Air Force was well received by physicians and patients (Runyan, Fonseca, & Hunter, 2003) and was shown to be effective for targeting a broad range of clinical concerns (Bryan et al, 2012) including insomnia (Goodie, Isler, Hunter, & Peterson, 2009) and posttraumatic stress disorder (Cigrang et al, 2011). A morning in the life of a BHC. As described above, the PCBH model of integrated primary care requires substantial shifts in the practice of most psychologists who have trained and practiced primarily in specialty mental health settings.…”
Section: Psychology Internship Training Programsmentioning
confidence: 97%